Algebras Satisfying Polynomial Identity of Degree Six that are Principal Train (European Journal of Pure and Applied Mathematics, 2023)
In this paper we study the class of algebras satisfying a polynomial identity of degree six that are principal train algebras of rank $3$ or $4$, for which we give the explicit form of the train equation. If the rank of $A$ is $n≥ 5$ in general, we provide the form of the train equation in some cases.
Keywords: Peirce decomposition; principal train algebra; polynomial identity; idempotent